Hot press sintering effects and wear resistance of the Al-B4C composite coatings of an AA-2024 alloy - Ozay, Cetin; Karlidag, Omer Etem (Walter de Gruyter Gmbh, 2021)
In this study, the surface of AA-2024 alloy substrate was coated with an Al-B4C reinforced composite using hot press sintering. Al and B4C powders were synthesized by mechanical alloying. To this end, four samples were prepared. As a reference sample, AA-2024 substrate was coated with pure Al powder under 110 MPa pressure. In the other samples, the AA-2024 substrate was coated with metal matrix composites (MMCs) contained in Al-5 wt.-% B4C at 90, 110 and 130 MPa. The microstructure of the transition zone formed between the AA-2024 substrate and the coating layer of the coated samples, the microstructure of the Al/B4C MMCs coating, the macro hardness, the linear reciprocating and forth wear resistance of the coating layer were investigated. In addition, an optical microscope (OM), scanning electro microscope (SEM) images and EDS analysis of the microstructure were used. It was observed that the B4C powders were homogeneously distributed in the Al matrix in the microstructure of the coating layer. It was also found that the gaps between the grains in the microstructure of the coating layer and their size decreased with an increase in pressing pressure. Accordingly, it was concluded that macro hardness increased and weight loss decreased.
Keywords: Hot press sintering; Al-B4C AMMCs; coating; wear resistance